How to make the best Ganjang Gejang: The Missional Church Movement in Korea: Evaluation and Proposal - Chung, Seung-hyun (Ecclesial Futures, 2023)
In Korean Christianity, interest in missional church has almost exploded in the past 15 years, with two main streams of ideas. One emphasizes that a local church should reflect the missionary nature of the Triune God in a series of activities such as worship, preaching, praise and Bible study. The other insists that since the God of scripture always calls and sends people, church members should also go to their local community. This paper reviews the current discussion on missio Dei in Korea and the creation theology of Jürgen Moltmann. Moltmann states that God’s creation continues until the end and God’s ultimate purpose is to fellowship with all creation. Kong3al Community and Ilbeot Church, located in Gang-hwa Island, South Korea, practise such fellowship between human and human, human and nature, and creation and God. For the missional church movement to proceed fully in Korea, both streams should engage each other through the osmosis of the economy of salvation and the work of creation.